Effect of aqueous extract of maca on cognitive function in weaning infant rats - Oré, Raquel (2011)
Background: Maca, Lepidium meyenii walp, is a plant that grows in Peruvian Andes’ highlands. It is used as food because of its nutritional value and its ethnical and medical properties related to fertility and vitality. Currently public interest has increased on food and dietetic supplements that contain active principles like polyphenol compounds with inhibitory effect on acetylcholinesterase and butyrylcholinesterase activities, thus improving cognitive functions through mechanisms yet unknown; for this reason maca has been proposed as an adaptogen that increases energy and resistance and diminishes stress. Objectives: To determine the energetic effect of yellow maca on memory and learning by biochemical tests, in an animal model of weaning rats. Design: Experimental study. Setting: Biochemistry and Nutrition Research Center, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biologic material: Weaning rats and aqueous yellow maca extract. Interventions: Weaning rats received yellow maca liquid extract (0.4 mg, 0.8 mg, and 1.2 mg/g de peso) during 15 days followed then by Morris spatial aquatic test. Brain samples were taken for biochemistry tests. Main outcome measures: Improvement of both learning and memory. Results: Butyrylcholinesterase inhibition was found with increasing dosis of maca except the group receiving 0.8 mg/g. Brain lipoperoxidation level (oxidative damage) decreased with increasing maca dosis; also time (s) in finding Morris platform test decreased with increasing yellow maca dosis. Brain total glutation concentration increased not significatively with maca supply. Conclusions: Maca liquid extract supplement improved learning and memory in experimental animals as well as brain antioxidant defenses.